Gambaran Alternatif Pengolahan Limbah Medis Dengan Proses Sterilisasi di Puskesmas - Nailul Hikmi (Yayasan Jompa Research and Development, 2022)
Medical waste is waste that results from the act of diagnosis and medical treatment of patients. Infectious medical waste includes the definition of waste related to patients requiring isolation of infectious diseases (intensive care) and laboratory waste related to microbiological examinations from polyclinics and infectious disease treatment/isolation rooms. The type of research used is descriptive. The object of research is solid medical waste in the form of gauze from the process of medical treatment for patients at the Puskesmas. The medical waste treatment process is carried out by inserting samples with a weight of each sample of 5 grams into a petridish. Three samples were treated with a temperature of 121 C and a time of 15 minutes, a temperature of 126 C with a time of 25 minutes and a temperature of 131 C with a time of 35 minutes. The total plate number of medical waste before treatment was 1300 CFU/Cm2 and the total plate number after treatment was 0 CFU/Cm2. It is expected that medical waste treatment with the sterilization method using an autoclave is utilized by the Puskesmas which is located far from the location of the destruction of medical waste with an incinerator.